2022
DOI: 10.3390/ijms232112783
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Glass-Ceramic Spray Deposition Technology Improving the Adhesive Performance for Zirconium-Based Dental Restorations

Abstract: Glass-ceramic spray deposition (GCSD) is a novel technique for coating lithium disilicate (LD) glass-ceramics onto zirconia through simple tempering steps. GCSD has been proven to improve the bonding of zirconia to resin cement, but the effect of etching time on GCSD and the long-term durability of the bond achieved remain unknown. The effects of air abrasion with aluminum particles (ABB) and air abrasion (GAB) or etching with 5.0% hydrogen fluoride (HF) for 20, 60, 90, and 120 s (G20, G60, G90, and G120) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The GCSD technique could produce a layer of glass-ceramic coatings with a thickness of approximately 11.78 μm on zirconia surfaces [ 23 ]. Previous studies have proved the improved bond strengths of GCSD on zirconia after etching with 5% HF for 90–120 s [ 22 , 23 ]. Herein, we demonstrated that 3Y-TZP with GCSD showed comparable SBSs with LDGC before thermocycling ( Table 2 ), which is partly consistent with previously published data [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The GCSD technique could produce a layer of glass-ceramic coatings with a thickness of approximately 11.78 μm on zirconia surfaces [ 23 ]. Previous studies have proved the improved bond strengths of GCSD on zirconia after etching with 5% HF for 90–120 s [ 22 , 23 ]. Herein, we demonstrated that 3Y-TZP with GCSD showed comparable SBSs with LDGC before thermocycling ( Table 2 ), which is partly consistent with previously published data [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved the improved bond strengths of GCSD on zirconia after etching with 5% HF for 90–120 s [ 22 , 23 ]. Herein, we demonstrated that 3Y-TZP with GCSD showed comparable SBSs with LDGC before thermocycling ( Table 2 ), which is partly consistent with previously published data [ 22 ]. Paradoxically, Kang et al [ 22 ] and Peng [ 23 ] reported that 3Y-TZP with GCSD showed higher SBSs than 3Y-TZP with APA using 50 μm Al 2 O 3 at 0.3 Mpa combined with MDP-containing primer (Z-Prime Plus).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations